Towards Understanding the EBV gp350-Complement Receptor 2 Interaction - Wheeler, Michael (URJ-UCCS: Undergraduate Research Journal at UCCS, 2020)
Complement Receptor 2 (CR2) is the obligate human host receptor for the Epstein Barr Virus (EBV). The viral surface glycoprotein 350 (gp350) is known to interact with CR2 on human immune cells, resulting in viral infection. EBV infection results in either, an asymptomatic response as a result of infant infection, or a symptomatic response clinically known as infectious mono resulting from infection later in life. Regardless of when the initial infection occurs, the virus will remain latent in the body until the immune system becomes compromised. This latency has been suggested to be related to many different cancers and diseases. Currently there are no therapies or vaccines against EBV. The results we present are the first steps in understanding the molecular interactions required for the infection of immune cells by the EBV. We have cloned and expressed the CR2 and gp350 protein and are currently in the process of analyzing the binding kinetics between them via bio-layer interferometry (BLItz) analysis. BLItz analysis has confirmed the binding of gp350 to CR2. Lowered salt concentrations will be tested to determine if a reduction in binding interference can occur. Crystallography will be used to analyze the protein-protein interactions of CR2 and gp350 to create a 3D structure of the protein binding complex.